2017
DOI: 10.3126/njb.v5i1.18870
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Herbs and Herbal Products Feed Supplements on Growth in Fishes: A Review

Abstract: The herbs and herbal products added to the feed cure many diseases, promote growth, reduce stress, improve immunity and prevent infections in fish under culture. The addition of herbs and herbal products in fish diet is cheaper and environmental friendly with low side effect to the fish and consumers. Hence, their use as drugs in disease management in aquaculture is gaining popular. They are better than various antibiotics and vaccines used in the treatment of diseases. The present review highlights the import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…Throughout the experimental period, feed intake was high among the plant substituted diets compared to the normal diet. A lot of evidence has been presented that fishes are especially sensitive to the quality of feed and the presence of dietary anti-nutritional factors (Shakya, 2017). One of the most commonly encountered problems with alternative vegetable protein sources in aquaculture feeding is the palatability of fish.…”
Section: Discussionmentioning
confidence: 99%
“…Throughout the experimental period, feed intake was high among the plant substituted diets compared to the normal diet. A lot of evidence has been presented that fishes are especially sensitive to the quality of feed and the presence of dietary anti-nutritional factors (Shakya, 2017). One of the most commonly encountered problems with alternative vegetable protein sources in aquaculture feeding is the palatability of fish.…”
Section: Discussionmentioning
confidence: 99%
“…The use of herbal substances is alternative prevention and curative that is environmentally friendly because the herbal substances will be easier to decompose in nature compared to antibiotics (Shakya, 2017). One of the herbal substances that can be used to overcome bacterial diseases is banana plant-based powder.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated the efficacy of herbal extracts on fish to attenuate stress response [ 1 ], improved immune system, enhanced gut tissue integrity [ 51 , 52 , 53 ], and increase feed digestibility and fish growth performance [ 1 , 54 ]. In this context, EOs have been studied for their several beneficial characteristics, such as antibacterial and anti-oxidant properties [ 55 ], and their ability to improve the feed conversion ratio by improved feed palatability [ 56 , 57 , 58 ], feed digestibility, and nutrient transport [ 57 ].…”
Section: Discussionmentioning
confidence: 99%